Analisis Kepuasan Pengguna Sistem SpoolTag pada Manajemen Informasi Pipe Spool Industri Fabrikasi Oil and Gas - Munir, Abdul; Arribathi, Abdul Hamid; Lubis, Arina Luthfini (Dinasti Research, 2026)
The oil and gas fabrication industry is characterized by a high level of complexity, requiring an information management system capable of supporting accurate, timely, and integrated pipe spool management. One of the tools used for this purpose is the spooltag system, which functions as a spool identification tool throughout the fabrication and installation processes. However, in practice, several issues are still encountered, including data inconsistencies, differences in standardization across projects, delays in locating spools, and the lack of an effective digital tracking system. This study aims to analyze user satisfaction with the pipe spool information management system and to identify existing problems as well as development needs related to the spooltag system in the oil and gas fabrication industry. This research employed a descriptive quantitative approach using a survey method through the distribution of online questionnaires based on a Likert scale to 20 respondents consisting of practitioners such as Piping Engineers, Fabrication Engineers, Construction Engineers, Material Controllers, Supervisors, and other related personnel. The data were analyzed descriptively using bar charts and respondent perception analysis, supported by the evaluation of open-ended responses. The findings reveal that the majority of respondents perceived the current spooltag system as beneficial for identifying spools in the field, facilitating material retrieval in laydown areas, supporting erection and installation activities, and improving coordination among departments. However, respondents also indicated that spooltag standardization still needs improvement, naming formats should be simplified and made more informative, and digital spool tracking systems as well as integration among drawing, fabrication, laydown, and installation processes are strongly required. Based on these findings, it can be concluded that the current spooltag system has provided significant benefits to project operations; however, further development toward a more standardized, digital, integrated, and user-friendly system is still necessary to enhance efficiency, accuracy, traceability, and productivity in oil and gas fabrication projects